One-Step Preparation of Functionalized (E)-Vinylsilanes from Aldehydes - Lim, D; Anderson, E (2011)
Functionalized (E)-vinylsilanes have been prepared in one step from a wide range of aldehydes, via a chromium(II)-mediated olefination with novel dihalomethylsilane reagents, in moderate to excellent yields and with excellent stereoselectivity. © 2011 American Chemical Society.